Comparison of reproducibility of single voxel spectroscopy and whole‐brain magnetic resonance spectroscopy imaging at 3T. (13th February 2018) - Zhang, Yue; Taub, Edward; Salibi, Nouha; Uswatte, Gitendra; Maudsley, Andrew A.; Sheriff, Sulaiman; Womble, Brent; Mark, Victor W.; Knight, David C.
Abstract : To date, single voxel spectroscopy (SVS) is the most commonly used MRS technique. SVS is relatively easy to use and provides automated and immediate access to the resulting spectra. However, it is also limited in spatial coverage. A new and very promising MRS technique allows for whole‐brain MR spectroscopic imaging (WB‐MRSI) with much improved spatial resolution. Establishing the reproducibility of data obtained using SVS and WB‐MRSI is an important first step for using these techniques to evaluate longitudinal changes in metabolite concentration. The purpose of this study was to assess and directly compare the reproducibility of metabolite quantification at 3T using SVS and WB‐MRSI in 'hand‐knob' areas of motor cortices and hippocampi in healthy volunteers. Ten healthy adults were scanned using both SVS and WB‐MRSI on three occasions one week apart. N‐acetyl aspartate (NAA), creatine (Cr), choline (Cho) and myo‐inositol (mI) were quantified using SVS and WB‐MRSI with reference to both Cr and H2 O. The reproducibility of each technique was evaluated using the coefficient of variation (CV), and the correspondence between the two techniques was assessed using Pearson correlation analysis. The measured mean (range) intra‐subject CVs for SVS were 5.90 (2.65‐10.66)% for metabolites (i.e. NAA, Cho, mI) relative to Cr, and 8.46 (4.21‐21.07)% for metabolites (NAA, Cr, Cho, mI) relative to H2 O. The mean (range) CVs for WB‐MRSI were 7.56 (2.78‐11.41)% for metabolites relative to Cr, and 7.79 (4.57‐14.11)% for metabolites relative to H2 O. Significant positive correlations were observed between metabolites quantified using SVS and WB‐MRSI techniques when the Cr but not H2 O reference was used. The results demonstrate that reproducibilities of SVS and WB‐MRSI are similar for quantifying the four major metabolites (NAA, Cr, Cho, mI); both SVS and WB‐MRSI exhibited good reproducibility. Our findings add reference information for choosing the appropriate 1 H‐MRS technique in future studies. Abstract : The reliability of metabolite quantification using single voxel spectroscopy (SVS) and whole‐brain MR spectroscopic imaging (WB‐MRSI) at 3T was directly compared in the present study. There was good reliability and comparable reproducibility for quantifying the four major metabolites (N‐acetyl‐aspartate (NAA), creatine (Cr), choline (Cho) and myo‐inositol (mI)) using both SVS and WB‐MRSI. Significant positive correlations (Pearson's r ranging from 0.6‐0.9) were observed between the two techniques when using Cr as the quantification reference.